1997
DOI: 10.1074/jbc.272.39.24717
|View full text |Cite
|
Sign up to set email alerts
|

The Acidic C-terminal Domain of rna1p Is Required for the Binding of Ran·GTP and for RanGAP Activity

Abstract: The small GTP binding protein Ran is an essential component of the nuclear protein import machinery whose GTPase cycle is regulated by the nuclear guanosine nucleotide exchange factor RCC1 and by the cytosolic GTPase activating protein RanGAP. In the yeasts Schizosaccharomyces pombe and Saccharomyces cerevisiae the RanGAP activity is encoded by the RNA1 genes which are essential for cell viability and nucleocytoplasmic transport in vivo. Although of limited sequence identity the two yeast proteins show a conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 59 publications
2
30
1
Order By: Relevance
“…In mammalian RanGAPs, it consists almost entirely of glutamate and aspartate. Haberland et al (26), using C-terminal deletion mutants of Schizosaccharomyces pombe and Saccharomyces cerevisiae RanGAP and phosphate release assays, suggested that the C terminus is required for GAP activity and Ran binding. It should be noted that the structure of RanGAP was not available at that time (30) and that those deletion constructs were based on incorrectly assigned LRRs which in turn were based on the structure of RNase A inhibitor (37).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammalian RanGAPs, it consists almost entirely of glutamate and aspartate. Haberland et al (26), using C-terminal deletion mutants of Schizosaccharomyces pombe and Saccharomyces cerevisiae RanGAP and phosphate release assays, suggested that the C terminus is required for GAP activity and Ran binding. It should be noted that the structure of RanGAP was not available at that time (30) and that those deletion constructs were based on incorrectly assigned LRRs which in turn were based on the structure of RNase A inhibitor (37).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, while RanBDs were shown to costimulate RanGAP-catalyzed hydrolysis (10,72), the structure of the ternary complex and multiple turnover kinetics suggested that the catalytic machinery was entirely located on Ran. Previously, it was suggested that the conserved C-terminal highly acidic region of RanGAP is required for Ran binding and for stimulation of GTP hydrolysis (26). Although this acidic region was not visible in the structure, it did not appear to participate in catalysis.…”
mentioning
confidence: 99%
“…The func-tional roles of the acidic domain of RanGAP1 continue to remain controversial, despite the fact that the domain is conserved over different phyla. The acidic domain of yeast rna1p was reported to be essential for Ran-GTP binding and/or RanGAP1 activity (Haberland et al, 1997, Traglia et al, 1989. A recent report, however, indicated that the acidic region of yeast Rna1p was dispensable for GAP activity and Ran binding, but instead, was essential for microtubule formation during mitosis (Seewald et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Two good candidate effectors are Ran GTPase and Pins. LRRs are known to physically interact with Ran, which promotes spindle assembly through several target proteins (Dasso, 2001;Haberland et al, 1997;Haberland and Gerke, 1999). For example, Ran stimulates the activity of NuMA (a microtubule motor accessory protein that promotes spindle assembly) by destabilizing inhibitory complexes associated with NuMA (Dasso, 2001;Dasso, 2002;Nachury et al, 2001;Wiese et al, 2001).…”
Section: Distinct Scrib Domains Regulate Cortical and Basal Targetingmentioning
confidence: 99%